Convalescent human IgG, but not IgM, from COVID-19 survivors confers dose-dependent protection against SARS-CoV-2 replication and disease in hamsters - King, Hannah A. D.; Dussupt, Vincent; Mendez-Rivera, Letzibeth; Slike, Bonnie M.; Tran, Ursula; Jackson, Nathan D.; Barkei, Erica; Zemil, Michelle; Tourtellott-Fogt, Emily; Kuklis, Caitlin H.; Soman, Sandrine; Ahmed, Aslaa; et al. (Frontiers in Immunology, 2023)
Antibody therapeutic strategies have served an important role during the COVID-19 pandemic, even as their effectiveness has waned with the emergence of escape variants. Here we sought to determine the concentration of convalescent immunoglobulin required to protect against disease from SARS-CoV-2 in a Syrian golden hamster model. Total IgG and IgM were isolated from plasma of SARS-CoV-2 convalescent donors. The IgM preparation was found to have 25-fold greater neutralization potency than IgG. Dose titrations of IgG and IgM were infused into hamsters 1 day prior to challenge with SARS-CoV-2 Wuhan-1. IgG infusion protected hamsters from disease in a dose-dependent manner, with detectable serum neutralizing titers correlating with protection. Despite a higher in vitro neutralizing potency, IgM failed to protect against disease when transferred into hamsters. This study adds to the growing body of literature that demonstrates neutralizing IgG antibodies are important for protection from SARS-CoV-2 disease, and confirms that polyclonal IgG in sera can be an effective preventative strategy if the neutralizing titers are sufficiently high. In the context of new variants, against which existing vaccines or monoclonal antibodies have reduced efficacy, sera from individuals who have recovered from infection with the emerging variant may potentially remain an efficacious tool.